Health Care for Persistent Somatic Symptoms Across Europe: A Qualitative Evaluation of the EURONET-SOMA Expert Discussion - Kohlmann, Sebastian; Löwe, Bernd; Shedden-Mora, Meike C. (Frontiers in Psychiatry, 2018)
Background. Persistent somatic symptoms (PSS) are frequent but often remain under-recognized and under-treated. Despite overlapping recommendations in European guidelines, there is presumably a heterogeneity in the actual health care situation across Europe. The aim of this expert discussion within the European Research Network on Persistent Somatic Symptoms (EURONET-SOMA) was to compare health care for PSS across Europe, to illustrate commonalities and differences, and to discuss challenges for a pan-European research agenda. Methods. A case vignette fulfilling ICD-10 criteria of undifferentiated somatization disorder was presented to 24 experts from 9 European countries, who completed a semi-structured assessment regarding the typical health care (i.e., diagnostic procedures, treatment and health care delivery). A qualitative analysis was conducted using the assessments, video-transcripts, and additional expert interviews. Results. Terms used for PSS largely vary. Across all countries, primary care physicians serve as gate keepers for further diagnostic and treatment procedures. Apart from this commonality, there is a large variability in health care routines. Health care is often far from being guideline-based and appears to be inefficiently structured in clinical routine. Experts concluded that PSS appear to be a non-identified patient group within many European health care systems. Conclusions. To overcome the gap between evidence-based guidelines and clinical reality, three key challenges were identified: 1) Defining a clinically useful, acceptable, and non-stigmatizing diagnostic term, 2) implementing guideline recommendations into routine care, 3) developing effective dissemination strategies. The results advocate for a European research agenda to investigate the actual European health care situation.